Thermo-hydrodynamic analysis of large-eccentricity hydrodynamic bearings with texture on journal surface. (October 2018) - Wang, Lin; Han, Zhanhai; Chen, Guoding; Su, Hua
To improve the performance of a heavy-loaded and high-speed hydrodynamic bearing, partial texture is designed on the journal surface. A three-dimensional thermo-hydrodynamic analysis model is developed based on the computational fluid dynamics method. Thermal conduction of bearing bush and journal, heat convection on the air-bearing surface, viscosity–temperature effect, and cavitation effect are taken into account. Performance of textured and un-textured high-speed journal bearing under different eccentricity ratios and different external loads is compared. The results indicated that partial texture on journal surface can play a positive role for large eccentricity ratio conditions in this study, and the textured bearing has a higher load carrying capacity, a lower maximum oil pressure, and a lower oil temperature rise than the un-textured bearing based on an optimal design of texture.